A Concise Tool for Measuring Care Coordination from the Provider's Perspective in the Hospital Setting. Issue 10 (23rd August 2017) - Weston, Christine M.; Yune, Sehyo; Bass, Eric B.; Berkowitz, Scott A.; Brotman, Daniel J.; Deutschendorf, Amy; Howell, Eric E.; Richardson, Melissa B.; Sylvester, Carol; Wu, Albert W.
Abstract : BACKGROUND: To support hospital efforts to improve coordination of care, a tool is needed to evaluate care coordination from the perspective of inpatient healthcare professionals. OBJECTIVES: To develop a concise tool for assessing care coordination in hospital units from the perspective of healthcare professionals, and to assess the performance of the tool in measuring dimensions of care coordination in 2 hospitals after implementation of a care coordination initiative. METHODS: We developed a survey consisting of 12 specific items and 1 global item to measure provider perceptions of care coordination across a variety of domains, including teamwork and communication, handoffs, transitions, and patient engagement. The questionnaire was distributed online between October 2015 and January 2016 to nurses, physicians, social workers, case managers, and other professionals in 2 tertiary care hospitals. RESULTS: A total of 841 inpatient care professionals completed the survey (response rate = 56.6%). Among respondents, 590 (75%) were nurses and 37 (4.7%) were physicians. Exploratory factor analysis revealed 4 subscales: (1) Teamwork, (2) Patient Engagement, (3) Handoffs, and (4) Transitions (Cronbach's alpha 0.84‐0.90). Scores were fairly consistent for 3 subscales but were lower for patient engagement. There were minor differences in scores by profession, department, and hospital. CONCLUSION: The new tool measures 4 important aspects of inpatient care coordination with evidence for internal consistency and construct validity, indicating that the tool can be used in monitoring, evaluating, and planning care coordination activities in hospital settings.